Mapping Diversity in Milan. Historical Approaches to Urban Immigration - John Foot (Fondazione Eni Enrico Mattei (FEEM), 2006)
An historical and spatial approach is crucial to the understanding of any city. Waves of immigration and population movements from different sources have constructed the cultural mix of this financial, industrial and market city over time. To focus just on the new foreign immigration into Milan over the last 25 years or so risks omitting the deep historical fissures created by previous (and bigger) waves of population movements the traces left by these populations in the urban fabric and their role in subjective experience. Moreover, the historical and spatial comparison of various types and moments of population movement can help us to understand the changes to this city at macro and micro-levels. This paper uses a mixture of approaches in order to understand and map diversity in Milan, its province and its region. It is intended as a discussion paper to be looked at in conjunction with the work and arguments laid out in other research projects and published work. Methodologies used in this paper range from straightforward historical research (using documents and archives) to photography, micro-history (the examination of one small area in this case one housing block) and oral historical interviews.
Keywords: 330; Immigration; Urban Space; Periphery (Periferia); Memory; Housing